Total quality management : a strategy for school development - Mashaba, Sebakane William (My University, 2006)
The aim of this study is to investigate whether Total Quality Management strategy can address the problem of school development within the previously disadvantaged schools at Sabie Circuit, Mpumalanga Province. In order to realize this aim, sixty-four respondents from eight schools, were given questionnaires as the data collection techniques. To ensure validity of the questionnaires, a pilot study was conducted in one of the primary schools. Findings of the study were used to make recommendations to principals, educators and parents who are members of school governing bodies. The researcher identified insufficient time as a limitation of the study because the researcher is a part time student.
Thesis (M.Ed.) -- University of Limpopo, 2006
Keywords: Total quality management strategy; School development; Sabie Circuit; Mpumalanga Province; Total quality management -- South Africa; School management and organization -- South Africa